2022
DOI: 10.1002/ajh.26620
|View full text |Cite
|
Sign up to set email alerts
|

Treosulfan compared with reduced‐intensity busulfan improves allogeneic hematopoietic cell transplantation outcomes of older acute myeloid leukemia and myelodysplastic syndrome patients: Final analysis of a prospective randomized trial

Abstract: The phase III study was designed to compare event-free survival (EFS) after treosulfanbased conditioning with a widely applied reduced-intensity conditioning (RIC) busulfan regimen in older or comorbid patients with acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS) undergoing allogeneic hematopoietic cell transplanta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…Recently, a phase III randomized study was published, which compared RIC Tre/Flu and Flu/Bu2 RIC regimen for AML/MDS patients, 50–70 years or younger patients with significant comorbidities (HCT‐CI >2). The results revealed that 3‐year EFS and OS were superior in the Tre/Flu group (59.5% and 49.7%; p = .0006, OS 66.8% and 56.3%; p = .0037 respectively) 46 . However, it remains unclear if treosulfan‐based conditioning can outperform other commonly used melphalan‐based containing regimens.…”
Section: Conditioning Regimens For Transplantationmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, a phase III randomized study was published, which compared RIC Tre/Flu and Flu/Bu2 RIC regimen for AML/MDS patients, 50–70 years or younger patients with significant comorbidities (HCT‐CI >2). The results revealed that 3‐year EFS and OS were superior in the Tre/Flu group (59.5% and 49.7%; p = .0006, OS 66.8% and 56.3%; p = .0037 respectively) 46 . However, it remains unclear if treosulfan‐based conditioning can outperform other commonly used melphalan‐based containing regimens.…”
Section: Conditioning Regimens For Transplantationmentioning
confidence: 98%
“…The results revealed that 3-year EFS and OS were superior in the Tre/Flu group (59.5% and 49.7%; p = .0006, OS 66.8% and 56.3%; p = .0037 respectively). 46 However, it remains unclear if treosulfanbased conditioning can outperform other commonly used melphalanbased containing regimens. A summary of conditioning regimens used for transplantation of MDS patients is presented in Table 6.…”
Section: Conditioning Regimens For Transplantationmentioning
confidence: 99%
“…While comparative data of RIC regimens is lacking in CLL, a CIBMTR analysis of 1,823 patients undergoing RIC allogeneic HCT for non-Hodgkin lymphoma (NHL) found that Flu-Bu2 and fludarabine-cyclophosphamide (Flu-Cy) were associated with lower NRM and favorable OS compared to Flu-Mel140mg/m 2 ( 87 ). There is also growing interest in the use of treosulfan as a low-toxicity alternative to busulfan in RIC regimens, and a randomized trial in AML/MDS found that fludarabine-treosulfan (Flu-Treo) was associated with improved NRM and OS compared to Flu-Bu2 ( 88 , 89 ). Preliminary data suggest that Flu-Treo may also be a viable conditioning regimen in NHL ( 90 , 91 ), but confirmation in larger studies is required.…”
Section: Conditioning Regimensmentioning
confidence: 99%
“…ATG was administered in addition to PTCy as GVHD prophylaxis in 13% of TBF and 11% of Treo patients, respectively. Median follow-up was 15 (range, 12-24) and 18 (range, [14][15][16][17][18][19][20][21][22] months in TBF and Treo, respectively.…”
Section: Patient Disease and Transplant Characteristicsmentioning
confidence: 99%